2004
DOI: 10.1590/s1519-69842004000400010
|View full text |Cite
|
Sign up to set email alerts
|

The larval midgut of Anticarsia gemmatalis (Hübner) (Lepidoptera: Noctuidae): light and electron microscopy studies of the epithelial cells

Abstract: The morphology of the midgut epithelium cells of Anticarsia gemmatalis (Hübner) larvae is described by light and transmission electron microscopy. The midgut of A. gemmatalis is the largest portion of the digestive tract, with three distinct regions: proximal, media and distal. Its wall is formed by pseudostratified columnar epithelial tissue having four cell types: columnar, goblet, regenerative, and endocrine cells. The columnar cells are numerous and long, with the apical portion showing many lengthy microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 16 publications
7
35
0
4
Order By: Relevance
“…The general morphology of midgut epithelium in larvae of D. saccharalis is similar to that described for many Lepidoptera such as Manduca sexta L. (Cioffi 1979) e Erynnis ello L. (Santos et al 1984) (Sphingidae), Spodoptera frugiperda Smith (Jordão et al 1999) and Anticarsia gemmatalis Hübner (Levy et al 2004) (Noctuidae), among many other species (for a review, see Lehane & Billingsley 1996).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The general morphology of midgut epithelium in larvae of D. saccharalis is similar to that described for many Lepidoptera such as Manduca sexta L. (Cioffi 1979) e Erynnis ello L. (Santos et al 1984) (Sphingidae), Spodoptera frugiperda Smith (Jordão et al 1999) and Anticarsia gemmatalis Hübner (Levy et al 2004) (Noctuidae), among many other species (for a review, see Lehane & Billingsley 1996).…”
Section: Discussionsupporting
confidence: 64%
“…Few studies describe the morphology of these projections under a light microscope (Caetano & Zara 2001, Lello & Vieira 2001, Levy et al 2004, Ferreira & Cruz-Landim 2005; and although the authors did not emphasize variability in the number of cytoplasmic protrusions dependent on the localization of columnar cells in the midgut, the morphological aspects described are similar to those observed in D. saccharalis. Our ultrastructural observations show that the scarce cytoplasmic protrusions of the anterior region exhibit microvilli on part of its surface and that these are absent in those of the posterior region, where its surface becomes smooth.…”
Section: Discussionmentioning
confidence: 99%
“…These effects have also been described to other insect species as Ephestia küehniella (Pyralidae) (Smith et al 1969); Apis mellifera (Apidae) (Jimenez & Gilliam 1990); Hyalophora cecropia (Saturniidae) (Anderson & Harvey 1996), and Anticarsia gemmatalis (Noctuidae) (Levy et al 2004;Knaak & Fiuza 2005). These authors suggested that the phenomenon of cytoplasm loss is probably correlated to cell degeneration in epithelial renewal.…”
Section: Resultsmentioning
confidence: 74%
“…These patterns occur due to high enzyme secretion activity in the midgut in an attempt to restore the lining that is being attacked (Terra & Ferreira 1994;Cristofoletti et al 2000;Levy et al 2004). Billingsley & Lehane (1996) and Levy et al (2004) report morphological aspects similar to those of S. frugiperda regenerative cells that are responsible for the process of lining cell recovery. It is believed that the midgut epithelial cells, when undergoing massive loss during digestion or in cases of necrosis, are replaced by mitotic activity from the regenerative cells.…”
Section: Resultsmentioning
confidence: 98%
“…In Brazil, Anticarsia gemmatalis Hübner 1818 (Lepidoptera, Noctuidae) is considered the key pest of soybean (Panizzi and Corrêa-Ferreira, 1997;Levy et al, 2004;Monnerat et al, 2007). A. gemmatalis, also known as velvetbean caterpillar, attack the aerial parts of plants (Gallo et al, 2002), hampering their development and thus causing losses in grain production (Morales et al, 1995).…”
Section: Introductionmentioning
confidence: 99%